Non-accidental harms ('abuse') in athletes with impairment ('para athletes'): a state-of-the-art review. Issue 3 (25th April 2019) - Tuakli-Wosornu, Yetsa A; Sun, Qisi; Gentry, Mark; Ona Ayala, Kimberly E; Doolan, Fiona C; Ottesen, Taylor D; Caldwell, Blake; Naushad, Nida; Huang, Patrick; Kirby, Sandi
Abstract : Objective: Para athletes reap significant health benefits from sport but are vulnerable to non-accidental harms. Little is known about the types and impacts of non-accidental harms Para athletes face. In this literature review, we summarise current knowledge and suggest priorities for future research related to non-accidental harms in Para athletes. Design: Six electronic databases were searched between August and September 2017. 2245 articles were identified in the initial title/abstract review, and 202 records were selected for full-text review following preliminary screening. Two independent examiners evaluated each full text, and eight citations were selected based on inclusion/exclusion criteria. Data sources: MEDLINE, Embase, PsycInfo, Cumulative Index to Nursing and Allied Health Literature, Scopus and Academic Search Premier. Eligibility criteria for selecting studies: Inclusion criteria: (A) human participants; (B) written in English; (C) descriptive, cohort and case series, case–control, qualitative, mixed methods studies and all clinical trials; and (D) data pertain to harassment/abuse of youth, recreational, collegiate, national-level and/or elite-level athletes with a physical and/or intellectual impairment. Results: Most studies focused on young, visually impaired athletes and approximately half of all studies described high rates of bullying and its social implications. One study confirmed remarkably high rates of psychological, physical and sexual harms in Para athletes, compared with able-bodied peers. Conclusions: Bullying in young, visually impaired athletes is described most commonly in the available literature. Due to the limited amount of data, the prevalence of non-accidental harms in Para athletes remains unclear and information on trends over time is similarly unavailable.